COMPARATIVE STUDY OF FINANCIAL PERFORMANCE AND MARKET PERFORMANCE IN COMPANIES THAT ARE COMMITTED TO ISO 14001 IN THE MINING SECTOR ON THE INDONESIA STOCK EXCHANGE 2009-2014 - Saputra, Fendi; Zulkifli, Zulkifli (International Journal of Business, Law, and Education, 2023)
This study examines the financial performance and market performance differences between companies certified to ISO 14001 and those not certified to ISO 14001. The management's environmental commitment is measured using the company's ownership of the ISO 14001 certificate. The financial performance is measured by using the Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Return on Assets (ROA), while the market's performance is measured using the Price Earnings Ratio (PER) and the Market to-Book Value (MBV). The study population was a mining company listed on the Indonesia Stock Exchange 2009-2014, some 202 companies. The sampling method used was purposive sampling with criteria mining companies from 2009 to 2014, certified ISO 14001 and uncertified ISO 14001; present stock price information, the annual report, and financial statements are complete. Samples are 82 mining companies with a certificate of ISO 14001 and 96 mining companies that do not have a certificate of ISO 14001. Mechanical analysis of data from this study using independent sample t-test. The results showed that the mean financial performance and market performance of companies that are ISO 14001 is higher than those of companies not certified to ISO 14001. There are significant differences in the ratio of Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Market to Book Value (MBV).